A Harmonious Symphony of Fourth-Wave Coffee Culture: How The Relationship Between Coffee and Local Wisdom Contributes to Sustainability and Ethical Practices in Community - Maspul, Kurniawan Arif (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The relationship between coffee and culture is a complex and harmonious symphony through its local wisdom, with each element contributing to a larger, beautiful composition. Coffee has played a significant role in many cultures worldwide, symbolising hospitality, socialisation, and tradition. This relationship has also led to cultural exchange and innovation, with coffeehouses becoming centres of intellectual and artistic trade. Specialty coffee has brought a new level of sustainability to the industry, emphasising transparency, traceability, and ethical practices. This symbiotic relationship between culture and sustainability has created a unique and harmonious blend of social, cultural, and economic sustainability, promoting a more holistic and equitable world. Furthermore, Saudi Arabia has embraced the fourth wave of specialty coffee, recognising its potential to drive gastronomic growth in their creative economy SMEs. Small businesses like Sulalat and Camel Step have emerged as industry leaders, emphasising sustainability and transparency in the coffee supply chain. The Saudi government has also implemented initiatives to support small businesses in the specialty coffee industry, driving economic growth. The fourth wave of specialty coffee has created a new coffee culture in Saudi Arabia, focusing on sustainability and unique flavours. As the industry expands, it is expected to create new opportunities for entrepreneurs and drive economic growth in the country. Moreover, the specialty coffee industry in Saudi Arabia is driving diversity and promoting sustainability through initiatives such as fair pay and working conditions for coffee farmers, promoting sustainable farming practices, and reducing waste. The sector supports local coffee producers and roasters, fostering economic growth and entrepreneurship in the region; it also works with coffee farmers globally and promotes sustainable coffee farming practices. The industry is leveraging artificial intelligence and high-end machinery to improve coffee production and reduce the negative environmental impact of farming. The specialty coffee industry is committed to the United Nations’ Sustainable Development Goals (SDGs) by promoting social, economic and ecological sustainability. By focusing on these areas, the industry is creating a more sustainable and equitable coffee industry that benefits the global community. The relationship between coffee and culture is a complex and harmonious symphony through its local wisdom, with each element contributing to a larger, beautiful composition. Coffee has played a significant role in many cultures worldwide, symbolising hospitality, socialisation, and tradition. This relationship has also led to cultural exchange and innovation, with coffeehouses becoming centres of intellectual and artistic trade. Specialty coffee has brought a new level of sustainability to the industry, emphasising transparency, traceability, and ethical practices. This symbiotic relationship between culture and sustainability has created a unique and harmonious blend of social, cultural, and economic sustainability, promoting a more holistic and equitable world. Furthermore, Saudi Arabia has embraced the fourth wave of specialty coffee, recognising its potential to drive gastronomic growth in their creative economy SMEs. Small businesses like Sulalat and Camel Step have emerged as industry leaders, emphasising sustainability and transparency in the coffee supply chain. The Saudi government has also implemented initiatives to support small businesses in the specialty coffee industry, driving economic growth. The fourth wave of specialty coffee has created a new coffee culture in Saudi Arabia, focusing on sustainability and unique flavours. As the industry expands, it is expected to create new opportunities for entrepreneurs and drive economic growth in the country. Moreover, the specialty coffee industry in Saudi Arabia is driving diversity and promoting sustainability through initiatives such as fair pay and working conditions for coffee farmers, promoting sustainable farming practices, and reducing waste. The sector supports local coffee producers and roasters, fostering economic growth and entrepreneurship in the region; it also works with coffee farmers globally and promotes sustainable coffee farming practices. The industry is leveraging artificial intelligence and high-end machinery to improve coffee production and reduce the negative environmental impact of farming. The specialty coffee industry is committed to the United Nations’ Sustainable Development Goals (SDGs) by promoting social, economic and ecological sustainability. By focusing on these areas, the industry is creating a more sustainable and equitable coffee industry that benefits the global community.